2022
DOI: 10.1002/adsc.202200699
|View full text |Cite
|
Sign up to set email alerts
|

Rh(III)‐Catalyzed C−H Functionalization of N‐Nitrosoanilines with α‐Sulfonylcarbenes

Abstract: A Rh(III)-catalyzed ortho CÀ H functionalization of N-nitrosoanilines with α-sulfonylcarbenes had been developed. The reaction was carried out under mild conditions and the products were obtained with good to excellent yields. The diverse transformations of the products to ortho-functionalized anilines and nitrogen heterocycles were achieved. Furthermore, a cascade reaction of N-nitrosoanilines and α-sulfonyl-α-diazoketones provided 3-sulfonyl-indoles efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…On the basis of the above control experiments and preceding literature reports, 6,11 c ,14 a plausible mechanistic pathway was proposed (Scheme 8). The active catalyst I was formed through the reaction of [Cp*RhCl 2 ] 2 with AgSbF 6 and NaOAc.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…On the basis of the above control experiments and preceding literature reports, 6,11 c ,14 a plausible mechanistic pathway was proposed (Scheme 8). The active catalyst I was formed through the reaction of [Cp*RhCl 2 ] 2 with AgSbF 6 and NaOAc.…”
Section: Resultsmentioning
confidence: 74%
“…The use of combinatory additives AbSbF 6 /AgOAc led to a better yield (Table 1, entry 3). 6 Further improvement was achieved by the combination of AbSbF 6 /NaOAc (Table 1, entry 4). A screening of reaction solvents indicated that DCE is the best choice (Table 1, entry 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the single electron transfer (SET) of J occurred with an arylsulfinic acid anion I to generate a peroxy anion K along with the formation of II or III . In intermediate K , the peroxy anion attacks the sulfur in K while breaking SO double bond to form the quaternary intermediate L . Finally, the intramolecular elimination of L delivered the final product 4a , along with arylsulfonate.…”
Section: Resultsmentioning
confidence: 99%
“…Commercially available amines that lead to a corresponding nitrosamine that is also commercially available, stable, and facile to monitor analytically (MS and UV) are most suitable to use as a positive control (e.g., N-methylaniline). 24,27 Certain N-nitrosamines can form in solution as transient intermediates but are not sufficiently stable to be isolated. This can especially occur when the nitrosamine is unstable in the presence of water.…”
Section: Conditions For Evaluating Viability Of N-nitrosamine Formationmentioning
confidence: 99%